1989
DOI: 10.1002/j.1460-2075.1989.tb08574.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the 3′ terminus of tRNA to 23S rRNA in the ribosomal exit site actively promotes translocation.

Abstract: A key event in ribosomal protein synthesis is the translocation of deacylated tRNA, peptidyl tRNA and mRNA, which is catalyzed by elongation factor G (EF‐G) and requires GTP. To address the molecular mechanism of the reaction we have studied the functional role of a tRNA exit site (E site) for tRNA release during translocation. We show that modifications of the 3′ end of tRNAPhe, which considerably decrease the affinity of E‐site binding, lower the translocation rate up to 40‐fold. Furthermore, 3′‐end modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 27 publications
11
90
0
Order By: Relevance
“…The importance of interaction of the tRNA 39 end with the 2390 region is further strengthened by the results of modification-interference selection+ Among E site-specific nucleotides in 23S rRNA, only modification of C2394 interfered with binding of uncharged tRNA to the 50S subunit E site+ Therefore, C2394 is apparently the primary 23S rRNA residue responsible for establishing contacts with A76 of tRNA in the E site+ Besides C2394, modification of three other residues, G2252, U2506, and U2585, also destabilized the complex between the 50S subunit and deacylated tRNA+ These three residues were among those that were found to be essential for binding of peptidyl-tRNA in the P site in the previous modificationinterference experiments (Bocchetta et al+, 1998) and thus, in the current experiments their modification apparently interfered with binding of deacylated tRNA to the large subunit P site+ Though modification of A2451 with DMS was found previously to interfere with binding of peptidyl-tRNA to the P site of the 50S subunit, in experiments with deacylated tRNA, modification of A2451 did not preclude tRNA binding+ Thus, modification-interference results confirm the conclusion of Noller et al+ (1990), made on the bases of tRNA footprinting, that A2451 may interact with the aminoacyl moiety of the P site-bound tRNA+ Crosslinking experiments utilizing tRNA azidoderivatives placed the 39 end of the E site-bound tRNA near ribosomal protein L33 (Wower et al+, 1993(Wower et al+, , 2000+ At the same time, L33 was mapped close to C2394 (Osswald et al+, 1990)+ Therefore, the interaction between tRNA A76 and 23S rRNA C2394 could be mediated by L33+ This model seems unlikely, however, because deacylated tRNA binds efficiently to the socalled KSP particles and protects E site-specific C2394 (our unpubl+ results)+ KSP particles, which are prepared from Thermus aquaticus 50S subunits by treatment with proteinase K, SDS, and phenol, retain only a subset of large ribosomal subunit proteins and apparently lack L33 (Noller et al+, 1992;Khaitovich et al+, 1999)+ Thus, protein L33 appears to be dispensable for the interaction of the tRNA 39 end with C2394+ Footprinting and modification-interference results are compatible with a direct interaction of A76 of E sitebound tRNA and C2394 of 23S rRNA+ Because tRNA protects C2394 from DMS modification at N3 of the cytidine base and, furthermore, because binding of tRNA to the E site is abolished when C2394 is modified by DMS, it is reasonable to assume that N3 of C2394 participates directly in bond formation with A76 of tRNA+ Reduced binding of tRNA containing etheno A or formycin as a 39 terminal base suggests that N6 and N7 of A76 may be involved in bond formation+ These considerations can be accommodated by a model in which A76 of tRNA forms a reverse Hoogsteen pair with C2394 of 23S rRNA (Fig+ 5B), though other types of interaction between tRNA 39-terminal residue and C2394 are also possible+ Hoogsteen-type base pairing between A76 of tRNA and U2506 or U2585 in ribosomal A-and P-sites, respectively, was proposed previously (Porse et al+, 1996;Wower et al+, 1999)+ It was suggested previously that A76 may form a Watson-Crick base pair with U2111 (Lill et al+, 1988(Lill et al+, , 1989+ This hypothesis appears ...…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The importance of interaction of the tRNA 39 end with the 2390 region is further strengthened by the results of modification-interference selection+ Among E site-specific nucleotides in 23S rRNA, only modification of C2394 interfered with binding of uncharged tRNA to the 50S subunit E site+ Therefore, C2394 is apparently the primary 23S rRNA residue responsible for establishing contacts with A76 of tRNA in the E site+ Besides C2394, modification of three other residues, G2252, U2506, and U2585, also destabilized the complex between the 50S subunit and deacylated tRNA+ These three residues were among those that were found to be essential for binding of peptidyl-tRNA in the P site in the previous modificationinterference experiments (Bocchetta et al+, 1998) and thus, in the current experiments their modification apparently interfered with binding of deacylated tRNA to the large subunit P site+ Though modification of A2451 with DMS was found previously to interfere with binding of peptidyl-tRNA to the P site of the 50S subunit, in experiments with deacylated tRNA, modification of A2451 did not preclude tRNA binding+ Thus, modification-interference results confirm the conclusion of Noller et al+ (1990), made on the bases of tRNA footprinting, that A2451 may interact with the aminoacyl moiety of the P site-bound tRNA+ Crosslinking experiments utilizing tRNA azidoderivatives placed the 39 end of the E site-bound tRNA near ribosomal protein L33 (Wower et al+, 1993(Wower et al+, , 2000+ At the same time, L33 was mapped close to C2394 (Osswald et al+, 1990)+ Therefore, the interaction between tRNA A76 and 23S rRNA C2394 could be mediated by L33+ This model seems unlikely, however, because deacylated tRNA binds efficiently to the socalled KSP particles and protects E site-specific C2394 (our unpubl+ results)+ KSP particles, which are prepared from Thermus aquaticus 50S subunits by treatment with proteinase K, SDS, and phenol, retain only a subset of large ribosomal subunit proteins and apparently lack L33 (Noller et al+, 1992;Khaitovich et al+, 1999)+ Thus, protein L33 appears to be dispensable for the interaction of the tRNA 39 end with C2394+ Footprinting and modification-interference results are compatible with a direct interaction of A76 of E sitebound tRNA and C2394 of 23S rRNA+ Because tRNA protects C2394 from DMS modification at N3 of the cytidine base and, furthermore, because binding of tRNA to the E site is abolished when C2394 is modified by DMS, it is reasonable to assume that N3 of C2394 participates directly in bond formation with A76 of tRNA+ Reduced binding of tRNA containing etheno A or formycin as a 39 terminal base suggests that N6 and N7 of A76 may be involved in bond formation+ These considerations can be accommodated by a model in which A76 of tRNA forms a reverse Hoogsteen pair with C2394 of 23S rRNA (Fig+ 5B), though other types of interaction between tRNA 39-terminal residue and C2394 are also possible+ Hoogsteen-type base pairing between A76 of tRNA and U2506 or U2585 in ribosomal A-and P-sites, respectively, was proposed previously (Porse et al+, 1996;Wower et al+, 1999)+ It was suggested previously that A76 may form a Watson-Crick base pair with U2111 (Lill et al+, 1988(Lill et al+, , 1989+ This hypothesis appears ...…”
Section: Discussionmentioning
confidence: 82%
“…In the course of translation, tRNA interacts with the ribosome at three different sites+ Prior to formation of a new peptide bond, aminoacyl-and peptidyl-tRNA are positioned in the acceptor (A) and donor (P) sites, respectively+ After peptidyl transfer and translocation, newly deacylated tRNA is transferred to the exit (E) site+ Existence of the E site was realized considerably after the A and P sites were described (Rheinberger et al+, 1981;Grajevskaja et al+, 1982;Kirillov et al+, 1983)+ Significantly less is known about E site location, composition, interaction with tRNA, and function compared to the other two tRNA-binding sites+ Nevertheless, the E site is thought to play an important role in translation+ Binding of tRNA in the E site prior to its release from the ribosome may promote translocation (Lill et al+, 1986(Lill et al+, , 1989 and/or improve accuracy of translation (Geigenmuller & Nierhaus, 1990)+ The critical characteristic of the E site is its strong preference for a deacylated tRNA 39 end (Rheinberger et al+, 1981;Grajevskaja et al+, 1982;Kirillov et al+, 1983;Lill et al+, 1984;Parfenov & Saminsky, 1985)+ Modifications of the 39 terminal tRNA residue or its removal dramatically affect E site binding of tRNA, indicating the importance of the tRNA 39 end for binding in the E site (Lill et al+, 1988)+ The recently deduced X-ray crystallographic structure of the ribosome-tRNA functional complexes showed that in the E site, tRNA contacts the ribosome in three locations: the 39 end and T⌿C loop of tRNA make contacts with the large ribosomal subunit in the cleft between the central protuberance and the L1 stalk, and the anticodon loop interacts with the small subunit between the platform and the head (Cate et al+, 1999)+ Uncharged tRNA bound to the E site of Escherichia coli 70S ribosomes protects from chemical modification a specific set of bases in 23S rRNA, namely, U2111, G2112, G2116, A2169, and C2394 (Moazed & Noller, 1989)+ This evidence suggested a close proximity of tRNA to rRNA in the E site+ From this, and from the observation that modifications of the 39 terminal adenine of tRNA decreased tRNA binding to the E site, a base pairing between the 39 terminal A of tRNA and U2111 of 23S rRNA was proposed (Lill et al+, 1988)+ However, tRNA-protein interactions can contribute to tRNA binding in the E site as well+ tRNA probes carrying 2-azidoadenosine near their 39 ends could be crosslinked to the protein L33 in the ribosomal E site, suggesting that L33 may facilitate tRNA binding (Wower et al+, 1993)+ At the same time, the anticodon loop of the E site-bound tRNA was crosslinked to protein S11 and 16S rRNA, revealing the contacts between the tRNA anticodon arm and the small ribosomal subunit+ Consensus has not yet been reached on the extent of contribution of codon-anticodon interaction to the tRNA binding in the E site …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mutations at the conserved G2252 and G2253 of 23S rRNA, which may interact with the 3'-CCA end of tRNA, also affect codon reading at the ribosomal A site (32). Although the exact nature of the association of the 3'-CCA sequence with rRNA still needs to be clarified, it has been suggested that base pairing between the CCA sequence and a complementary sequence within the central loop of domain V of 23S rRNA is involved in tRNA binding to the peptidyltransferase center (6). Our results on the protein synthetic activity of the 3'-terminal mutants of tRNAval are consistent with this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…1). Chemical and nuclease protection studies indicate that the 3'-CCA sequence also functions in later steps of protein synthesis: in formation of a ternary complex between aminoacyl-tRNA, elongation factor Tu, and GTP (1) and in the binding of tRNA to 23S rRNA at the A, P, and E sites of the 50S ribosomal subunit during the elongation and translocation steps of the translation cycle (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…In the first step, which occurs spontaneously after formation of the peptide bond, the acceptor end of the peptidyl-tRNA moves relative to the large ribosomal subunit forming a hybrid particle in which the acceptor end is in the P-site with the anticodon still remaining in the A-site. Simultaneously the CCA end of the deacylated tRNA in the P-site moves over to the E-site and interacts with 23 S rRNA, probably by baisepairing [294]. In the second step, which is promoted by EF-G, the deacylated tRNA is completely transferred to the E-site and the translocation is completed by moving the anticodon end of the peptidyl-tRNA relative to the small ribosomal subunit.…”
Section: Interaction Of Eef-2 With Ribosomesmentioning
confidence: 99%